Towards the humanization of childbirth. The draft standard of maternal care in Poland - Nowakowska, Luiza (Polish Journal of Public Health, 2010)
The pretext for these considerations has become the standard of maternal care in Poland, submitted to public consultation on 21 January 2010 by the Ministry of Health. The text drew attention to the proposal of regulation to the minimization of medical intervention during childbirth, the rights of the patient and increase patient satisfaction with the care provided. Standard, through changes in this area, aims to reduce excessive medicalization of perinatal period. In the text medicalization was treated as a specific model of pregnancy and childbirth, which predominates in many Western countries, and is the subject of increasing criticism. This model denies childbirth as a holistic act – a social, psychological, cultural and physiological interpretation for the medical – as a condition threatening the woman and child, and requiring medical supervision in hospital. One of the manifestation of this sense of medicalization are technological-interventionist philosophy of birth, patologization of pregnancy and objectification of women. This model of pregnancy and childbirth is discussed in a broader context as a part of more general phenomenon on the borderland of medicine and social life, which in the social sciences is examined for several decades. Terms of medicalization as a process of appropriation of social space through treatment of complex phenomena in terms of biomedicine, mostly as a disease risk factor or disorder. Also focuses on the arguments cited by proponents of socialized, holistic model of care and support of women, complementary to the hospital system, essential for pregnancies at risk. One of the serious consequences of madicalization, that is, the lowering of tha status od midwives and reducing their autonomy in perinatal care have also been discussed.